Characteristics and ecological effects of dissolved organic matter released by the main causative macroalgae of green and golden tides in the yellow sea - Zhang, Tao; Sui, Junhui; Huo, Xunjie; Wen, Biqing; Ren, Jiayuan; Li, Shihu; Chen, Xiaocong (Frontiers in Marine Science, 2025)
Green and golden tides caused by Ulva prolifera and Sargassum horneri erupt annually along the coasts of China. During the late stages of algal blooms, massive macroalgal die-offs result in the release of dissolved organic matter (DOM), which can profoundly affect local marine environments and elemental cycles. However, studies addressing these impacts remain insufficient and urgently needed. This study investigates the two primary macroalgal contributors, Ulva prolifera and Sargassum horneri, by simulating their decay and DOM release in seawater using Bacteria-active (BA) and Bacteria-inhibited (BI) groups. The release characteristics of carbon, nitrogen, and phosphorus, as well as their effects on microbial communities, were analyzed. Results show that U. prolifera and S. horneri rapidly release DOM and nutrients during their decay. Significant differences in the quantity and rate of DOM and nutrient release were observed due to structural differences between the two macroalgae. Carbohydrates constitute the major component of the released organic matter and are rapidly utilized by microbes for growth and reproduction. Furthermore, the DOM and nutrients released by macroalgae reshape the composition of microbial communities in the marine microenvironment. This study provides new insights into the potential regional marine ecological impacts of green and golden tide outbreaks from a biogeochemical perspective.